Dermoscopy as an efficient aid to diagnose pigmentary and vascular component of periorbital melanosis: A cross‐sectional study. (21st June 2022) - Chhabra, Namrata; Khare, Soumil; Sachdev, Divya
Abstract: Introduction: Periorbital melanosis (POM) has a significant impact on quality of life. There is a dearth of literature regarding POM, especially in Asian population. Accurate classification of POM is contributory to the choice of therapy. The aim of this study was to assess the role of dermoscopy in etiologic classification of POM. Methods: Two hundred and fifty adult patients (age > 18 years) of POM were enrolled over a period of 2 years. POM was classified clinically and re‐evaluated based on their dermoscopic findings (pattern of pigmentary and vascular involvement, surface changes). Results: Pigmented, vascular, structural, and mixed types of POM represented 6.4%, 4.8%, 0.4%, and 88.4%, respectively. Dermoscopy was found to be statistically more accurate in classifying pigmentary and vascular types of POM as compared to clinical examination with the naked eyes ( p‐ value <0.05). Patchy or post‐inflammatory pigmentation was the most common pigmentary pattern on dermoscopy (53.8%) followed by pseudoreticular (37.1%) and mixed pattern (9.1%). 80.4% patients had vascular involvement of which the most common vascular pattern was telangiectasia (58.8%). Wrinkling or increased skin laxity as a cause of shadow effect was found in 52% patients. Diffuse erythema and scaling suggestive of subtle inflammation was detected in 47.6% patients on dermoscopy. Conclusion: Dermoscopy as a diagnostic modality is more accurate in detecting pigmentary and vascular causes of POM and subtle signs of active inflammation in the form of erythema and scaling which is difficult to detect clinically. The major limitations of this study were lack of correlation of dermoscopic findings with the histological findings and the absence of any control group for comparison.